M. tuberculosis PknG manipulates host autophagy flux to promote pathogen intracellular survival. Issue 3 (4th March 2022) - Ge, Pupu; Lei, Zehui; Yu, Yang; Lu, Zhe; Qiang, Lihua; Chai, Qiyao; Zhang, Yong; Zhao, Dongdong; Li, Bingxi; Pang, Yu; Liu, Cui Hua; Wang, Jing
ABSTRACT: The eukaryotic-type protein kinase G (PknG), one of the eleven eukaryotic type serine-threonine protein kinase (STPK) in Mycobacterium tuberculosis (Mtb), is involved in mycobacterial survival within macrophages, presumably by suppressing phagosome and autophagosome maturation, which makes PknG an attractive drug target. However, the exact mechanism by which PknG inhibits pathogen clearance during mycobacterial infection remains largely unknown. Here, we show that PknG promotes macroautophagy/autophagy induction but inhibits autophagosome maturation, causing an overall effect of blocked autophagy flux and enhanced pathogen intracellular survival. PknG prevents the activation of AKT (AKT serine/threonine kinase) via competitively binding to its pleckstrin homology (PH) domain, leading to autophagy induction. Remarkably, PknG could also inhibit autophagosome maturation to block autophagy flux via targeting host small GTPase RAB14. Specifically, PknG directly interacts with RAB14 to block RAB14-GTP hydrolysis. Furthermore, PknG phosphorylates TBC1D4/AS160 (TBC1 domain family member 4) to suppress its GTPase-activating protein (GAP) activity toward RAB14. In macrophages and in vivo, PknG promotes Mtb intracellular survival through blocking autophagy flux, which is dependent on RAB14. Taken together, our data unveil a dual-functional bacterial effector that tightly regulates host autophagy flux to benefit pathogen intracellular survival. Abbreviations: AKT: AKT serine/threonine kinase; ATG5: autophagy related 5; BMDMs: bone marrow-derived macrophages; DTT: dithiothreitol; FBS: fetal calf serum; GAP: GTPase-activating protein; MOI: multiplicity of infection; Mtb: Mycobacterium tuberculosis ; MTOR: mechanistic target of rapamycin kinase; OADC: oleic acid-albumin-dextrose-catalase; PC, phosphatidylcholine; PH: pleckstrin homology; PI3K: phosphoinositide 3-kinase; PknG: protein kinase G; PtdIns(3, 4, 5)P3 : phosphatidylinositol(3, 4, 5)-trisphosphate; SQSTM1: sequestosome 1; STPK: serine-threonine protein kinase; TB: tuberculosis; TBC1D4: TBC1 domain family member 4; TPR: tetratricopeptide repeat; ULK1: unc-51 like autophagy activating kinase 1; WT: wild-type